Staff Appraisal Systems and Organisational Performance: The Moderating Role of Employee Motivation in Health Centre IV - Kiconco Clare; James Kizza; Nakku Elizabeth Mirembe (East African Journal of Business and Economics, 2026)
This study addresses a critical gap in public health human resource management by examining the unmapped interactive mechanism between performance accountability and workforce psychology within primary healthcare settings. While existing literature heavily treats performance evaluations as a mechanical process, this study investigates the moderating role of employee motivation in the relationship between staff appraisal systems and organisational performance across Health Centre IV facilities. Utilising an explanatory cross-sectional survey design, quantitative data were collected from a stratified random sample of 150 clinical, administrative, and auxiliary professionals. The estimation was done using the Hierarchical Moderated Multiple Regression (MMR) executed using mean-centred baseline vectors to eliminate structural multicollinearity, with all ordinary least squares assumptions verified through post-estimation diagnostic testing (Mean VIF = 1.31; Breusch-Pagan p = 0.211; Ramsey RESET p = 0.337). The empirical results revealed that while both staff appraisals (β = 0.156, p = 0.013) and employee motivation (β = 0.289, p < 0.001) exert significant direct positive effects on institutional outcomes, the study's primary originality lies in confirming a powerful, positive interaction effect (β = 0.172, t = 2.65, p = 0.009). This original finding proves that employee motivation functions as a catalyst that amplifies the positive impact of performance appraisal systems on healthcare delivery. Healthcare organisations must transition from treating performance reviews as rigid compliance exercises and instead use them to drive structural incentives like public recognition, professional development, and permanent contract absorption